Adventitious reinforcement during long‐duration DRO exposure. Issue 3 (6th March 2020) - Rey, Catalina N.; Betz, Alison M.; Sleiman, Andressa A.; Kuroda, Toshikazu; Podlesnik, Christopher A.
Abstract : Differential reinforcement of other behavior (DRO) is a procedure often used to decrease problem behavior, but the processes responsible for behavior reduction are not well understood. This study assessed whether adventitious reinforcement of other behavior contributes to DRO effectiveness when, relative to previous research, DRO exposure is prolonged. Two response options were presented on a computer and target responding was reinforced on a variable‐ratio schedule. Response rates were then compared during DRO versus yoked variable‐time or extinction probes. Across 2 experiments, DRO decreased target responding and increased other responding more than control conditions. However, increases in other responding did not usually maintain despite target responding remaining at low levels. DRO might adventitiously reinforce other responses transiently but the decreases in target behavior could not be entirely explained by adventitious reinforcement of the other response. Instead, reductions in target responding likely depend on the discriminability of the DRO contingency.